Evoluzione della chirurgia sostitutiva di ginocchio - Cerulli, G. (Lo Scalpello - Journal, 2019)
THE EVOLUTION OF KNEE-REPLACEMENTThe advent of knee arthroplasty is one of the most significant advances in surgery. Engineering and biomechanicalinnovations have shown a fast and effective evolution, in order to satisfy increasing functional requirements. In thispaper, the most important steps of this fascinating story are presented. It is clear that biomechanical and tribologicalstudies have always represented the basis for the onset of minimally invasive surgery, with less complications andgreater patient satisfaction. This evolution concerns not only the design of components, but also the materials used.